Implementasi Kompetensi Guru Berbasis ESD : Connect, Collaborate, and Engage di SD - Purwadi, Juniar; Hamdu, Ghullam (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2021)
Education for Sustainable Development (ESD) is one of the efforts to achieve sustainability goals regarding the quality of education. Of course, the teacher is the main agent in the success of this ESD. Therefore, the Asia Pacific ESD teacher competencies were formed called Connect, Collaborate, and Engage competencies, where teachers in schools, teachers in the community, and teachers as individuals are able to become teachers who have a leadership spirit. This study aims to provide information on the extent to which these competencies are implemented. The research method used is a combination research method. Data collection techniques by providing questionnaires and interviews conducted on elementary school teachers in Peunduey Village, Garut Regency. The questionnaires data was analyzed using the Winstep application with the Rasch model, for interview data it was analyzed using qualitative data analysis techniques according to Miles & Huberman. The results showed that the teacher with the highest ability was obtained by the 0LDTE teacher.Â  For the teacher with the lowest ability obtained by the 4PDRE teacher. The most difficult statement to implement is the L4 statement about finding the main stakeholders, meaning that teachers have not been able to relate and find the main stakeholders in education. The easiest statement to implement is the N4 statement about building trust and maintaining relationships, reciprocal care, and negotiating in conflict situations, which means the teacher always consults, maintains relationships, and solves problems in conflict situations. Overall competency implementation is 73%,.